2019
DOI: 10.31083/j.rcm.2019.02.31814
|View full text |Cite
|
Sign up to set email alerts
|

Anti-hypertensive efficacy of amlodipine dosing during morning versus evening: A meta-analysis

Abstract: A meta-analysis was performed to compare the antihypertensive efficacy of morning and evening dosing. Database of Pubmed, Embase, Cochrane, Web of Science CNKI, VIP, and Wanfang were searched up to December 2018. A total of 19 randomized control trials and 1215 participants were included in this meta-analysis. Administration time of amlodipine did not affect the office blood pressure (RR =-0.03, 95% CI-0.93-0.88, P = 0.96), daytime blood pressure (RR =-0.30, 95% CI-1.05-0.46, P = 0.44), 24 h mean blood pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…dipping status, resistant hypertension, etc.) [ 33 35 ]. Luo Y et al’s study demonstrated that 24 h BP profiles were normalized by taking amlodipine at the evening time [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…dipping status, resistant hypertension, etc.) [ 33 35 ]. Luo Y et al’s study demonstrated that 24 h BP profiles were normalized by taking amlodipine at the evening time [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 33 35 ]. Luo Y et al’s study demonstrated that 24 h BP profiles were normalized by taking amlodipine at the evening time [ 35 ]. In contrast with this study, all treated hypertensive patients in our study took CCBs in the morning.…”
Section: Discussionmentioning
confidence: 99%
“…The publicly open NIH program announcement (PA-19-034) detailing the classification and identification of 390 understudied druggable genomes was utilized to acquire the list of 261 candidate genes encoding GPCRs and ion channels. The associated literature survey was performed until 9 December 2021, with emphasis on published title words with (1) ion channels since 2017 [4,5,[9][10][11][12][13][14]16,26,27,30,33,[39][40][41][42]44,[46][47][48]53,54,59,61,[69][70][71][72][73][74][75][76][77][78][79][80], (2) ion channel blockers since 2017 [41,[81][82][83][84][85][86][87][88][89][90]…”
Section: Database Literature and Open-access Softwarementioning
confidence: 99%
“…Biomedicines 2022, 10, 594 2 of 21 Amlodipine besylate (brand name, Norvasc; Pfizer), which acts by blocking voltage-gated Ca 2+ channels [28][29][30][31][32], was patented in 1982, and it has since become one of the bestselling anti-hypertensive medications. In 2019, amlodipine was the fifth most prescribed medication in the United States (US) [33].…”
Section: Introductionmentioning
confidence: 99%
“…Impairments in these cells, which ensure proper blood flow and nutrient delivery to all organs, may result in atherosclerotic disease, hypertension, myocardial infarction, or other conditions. 10 Chemicals with KC5 include antihypertensive drugs, 11 arsenic, 12 cadmium, 13 and organophosphate pesticides. 14 …”
mentioning
confidence: 99%